2022
DOI: 10.1136/neurintsurg-2021-018192
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between 1-D, 2-D and 3-D carotid web quantification

Abstract: BackgroundCarotid webs (CaW) are now recognized as a cause of ischemic stroke in young patients. The thromboembolic potential appears related to the CaW’s morphology and consequent impact on local flow dynamics. We aim to evaluate the reliability of different measurement methods for the quantification of CaW and their relationship to symptomatic status, presence of large vessel occlusion stroke (LVOS), clot burden and final infarct volume.MethodsThis was a retrospective analysis of the local comprehensive stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies [ 14 , 18 , 21 , 22 ], our results indicated that gender and age differences in the two groups were statistically significant. In the CW group, 57.4% of the participants were women with an average age of 50.61 (± 12.49) years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies [ 14 , 18 , 21 , 22 ], our results indicated that gender and age differences in the two groups were statistically significant. In the CW group, 57.4% of the participants were women with an average age of 50.61 (± 12.49) years.…”
Section: Discussionsupporting
confidence: 92%
“…The CTA/HRMRI imaging scanning protocols were the same as in the prior study [ 18 ], and the details of protocols are available in Supplementary 1 . All CTA and HRMRI images were reviewed by two experienced radiologists (W.Z.…”
Section: Methodsmentioning
confidence: 99%
“…CTA is relatively inexpensive, easy to perform, and safe compared to magnetic resonance angiography (MRA) and DSA. During a study performed to clarify the relationship between the carotid web and ischemic stroke, the length, area, and volume of the carotid web were measured using CTA images of both symptomatic and asymptomatic cases ( Perry da Camara et al, 2022 ), resulting in the following observations among symptomatic and asymptomatic cases, respectively: mean carotid web lengths of 3.2 and 2.5 mm; median areas of 5.8 and 5.0 mm 2 ; and median volumes of 15.0 and 10.6 mm 3 . Additionally, that study noted that patients with a thinner carotid web (the longer intraluminal projection compared with the base) were more likely to have symptoms.…”
Section: Imaging Featuresmentioning
confidence: 99%
“…and the presence of a contralateral asymptomatic CaW was stated. As previously described, 21 linear length of CaW was also calculated and expressed in millimeters (mm). Stenosis resulting from CaW was measured according to the European Carotid Surgery Trial (ECST) method 22 and was expressed as a percentage.…”
Section: Collected Datamentioning
confidence: 99%